Pembuatan Tempat Cuci Tangan Sistem Injak Sebagai Upaya Pencegahan Covid-19 Di Desa Kalikajar - Koesuma, Sorja; Nabila, Dhia Azmi; Abdullah, Azar Rafliardi; Krismonanto, Wisnu; Arifin, Imam; Nursodik, Fajar; Pratiwi, Rizki Amalia; Susanto, Andika Dwi Cipta; Ananta, Aria Arga; Salfas, Muhammad (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The Covid-19 pandemic has caught the world's attention which hascaused various impacts on life. The spread of the virus takes placerapidly through droplets or physical contact to encouragegovernments to implement policies such as washing hands activitiesusing soap cleanly and correctly. Kalikajar village government asone of the villages that are exposed Covid-19 in Purbalingga alsohave appealed to the people to always washing hands with soap.However, the availability of hand washing facilities is still limitedand the conditions are alarming due to the lack of communitymaintenance. Therefore, as a form of community service, KuliahKerja Nyata (KKN) of Sebelas Maret University has initiative tocreate washbasin based on stepping system that can be used bypeople to get clean and healthy living. The service implementationstages include survey and identification of partner problems,preparation of problem solving frameworks, problem solving solutionprograms, implementation of service programs, monitoring andevaluation. Manufacture of washbasin through the manufacturingprocess and framework design, painting, assembly, and testing. Thewashbasin is distributed in several locations in Kalikajar Village,such as the Kalikajar Village Hall Office, Baitul Ghufron Mosque,and Baitul Muslimin Mosque. The distribution activites to severallocations had help from local residents, takmir mosques, and villageheads Kalikajar. Through this washbasin, the UNS KKN Team hopesthat the community and village government officials can develop andremind each other of the habit of washing hands so that it indirectlyhelps the government in preventing Covid-19 transmission in thesurrounding community.